Efektivitas Isolat-Isolat Bacillus sebagai Pengendali Penyakit Bulai dan Pemacu Pertumbuhan Tanaman Jagung pada Kondisi Terkontrol - Khoiri, Syaiful; Badami, Kaswan; Pawana, Gita; Utami, Ciwuk Sri (Rekayasa, 2021)
The main disease in maize is downy mildew caused by the fungus Peronosclerospora spp.. This pathogen can cause yield losses of up to 100%. Therefore, efforts to control this disease are continuously carried out, including technical culture, assembly of resistant plants, and use of synthetic fungicides. At the farm level, the use of metalaxyl, synthetic fungicides is the most common practice. On the other hand, it has been reported that some Peronosclerospora groups are starting to become resistant to metalaxyl. These problems lead to the need for alternative controls, for example with biological agents. Biological agents from bacterial groups have been developed to control plant disease, but for downy mildew is still limited. The purpose of this study is to screen and test Bacillus spp. ability to suppress downy mildew and promote the growth of maize. The assay was carried out on seeds by invitro to investigate growth-promoting reactions and also testing under controlled conditions in greenhouses to investigate the suppression ability of downy mildew disease development. The results showed B. polymyxa strain BP18, Bacillus subtilis strain BS41, Bacillus sp. strain BT1, and Bacillus sp. strains can stimulate the growth of corn seedlings and suppress downy mildew. The best isolate in suppressing downy mildew was Bacillus sp. strain BT1 with the smallest AUDPC value (3.94) and the highest protection index (82.71%). It is hoped that these results will find potential isolates and have the potential to be developed into biopesticides and biofertilizers.